2008
DOI: 10.1001/archpsyc.65.8.906
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E ε4 Allele Genotype and the Effect of Depressive Symptoms on the Risk of Dementia in Men

Abstract: Context The apolipoprotein E ε4 (APOE ε4) allele is a genetic risk factor for Alzheimer disease. Recently, depression has also become recognized as a risk factor for dementia. However, the possible effect of the APOE genotype on the association between depression and dementia is unexamined. Objective To examine the independent and combined effects of depression and APOE ε4 on the risk of dementia and its subtypes. Design The Honolulu-Asia Aging Study, a population-based prospective cohort study of Japanese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
83
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 55 publications
8
83
0
Order By: Relevance
“…For example, the association between smaller head circumference and incident AD was found to be stronger in the presence of APOE e4 (Borenstein Graves et al, 2001), and the risk of cognitive decline associated with vascular diseases was increased in the presence of APOE e4 (Haan et al, 1999). A recently published analysis from the HonoluluAsia Aging Study was the first, as far as we are aware, to test this in relation to depression as an exposure, finding that the elders with both depressive symptoms and APOE e4 had a markedly increased risk of dementia (Irie et al, 2008). Comparable results with other cognitive outcomes have also been reported.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, the association between smaller head circumference and incident AD was found to be stronger in the presence of APOE e4 (Borenstein Graves et al, 2001), and the risk of cognitive decline associated with vascular diseases was increased in the presence of APOE e4 (Haan et al, 1999). A recently published analysis from the HonoluluAsia Aging Study was the first, as far as we are aware, to test this in relation to depression as an exposure, finding that the elders with both depressive symptoms and APOE e4 had a markedly increased risk of dementia (Irie et al, 2008). Comparable results with other cognitive outcomes have also been reported.…”
Section: Discussionmentioning
confidence: 97%
“…It could, therefore, be hypothesized that there may be a synergistic effect of depression and APOE e4 on risk of dementia. In a recently published analysis of the Honolulu-Asia Aging Study, participants with depressive symptoms and APOE e4 at baseline had a 7-fold increased risk of dementia after 6 years follow-up compared with those with neither risk factor (Irie et al, 2008). Using data from a prospective community study of another East Asian (Korean) population, we sought to replicate this finding and to evaluate whether there were individual depressive symptoms where this interaction was most evident.…”
Section: Introductionmentioning
confidence: 98%
“…2,3 Several studies have reported that depression was associated with faster cognitive decline in carriers of the APOE-ε4 allele, a genetic marker for AD, compared to those without this genetic marker. 5,6 Depression may raise the risk of dementia because of biologic abnormalities associated with this affective illness, such as hypothalamic-pituitary axis dysregulation and high cortisol levels 7 , decreased homeostasis of the autonomic nervous system resulting in decreased heartrate variability 8 , increased platelet activation 9 , and an increase in pro-inflammatory factors. 10 Depression may also increase the risk of dementia because of its association with a higher risk for behavioral risk factors such as smoking, obesity, and sedentary lifestyle and vascular risk factors such as hypertension, hyperlipidemia, and diabetes.…”
mentioning
confidence: 99%
“…There are, however, inconsistent findings regarding this point. Some studies found an increased risk for older adults with depression to develop AD or major cognitive decline (Bassuk et al 1998;Cui et al 2007;Modrego and Ferrández 2004;Wilson et al 2008;Irie et al 2008;Saczynski et al 2010; Van den Kommer et al 2012), whereas others found an increased risk for people with AD to develop depression (Chen et al 1999;Vinkers et al 2004). There are also studies that did not find a longitudinal, but only a cross-sectional association between AD or severe memory decline and depression (Dufouil et al 1996;Burke et al 1988;Ganguli et al 2006;Zimprich et al 2003).…”
Section: Introductionmentioning
confidence: 99%